PENGARUH PENGANGGURAN TERHADAP DAYA BELI MASYARAKAT KALBAR - Zarkasi, Zarkasi (Khatulistiwa, 2014)
The problem of unemployment has become such a frightening scourge, especially in developing countries such as Indonesia. Unemployment has impact on people’s income per-capita, and income will subsequently have an impact on the people’s purchasing power. West Kalimantan is one of the provinces in Indonesia which is also experiencing the impact of economic disparity, i.e. unemployment. Employment, the less quality of human resources and labor in excess of available jobs is contributing to unemployment. This paper discusses the influence of unemployment on people’s purchasing power in West Kalimantan. Purchasing power can be seen from people’s spending per-capita rates from year to year. The data used in this paper includes that from 2002 through 2011 obtained from the publications of the Provincial Bureau of Statistics of West Kalimantan. Results of the study showed that the unemployment rate effect is negative and partially significant (individual) on people’s purchasing power. This suggests that when someone is not working or unemployed, it will affect their revenues, and reduced people's income will affect people’s purchasing power in West Kalimantan, Indonesia